A survey of consumer’ opinion about consumption and health benefits of fermented plant beverages in Thailand - Chaiyavat Chaiyasut (2018)
© 2018, Sociedade Brasileira de Ciencia e Tecnologia de Alimentos, SBCTA. All rights reserved. Fermented beverages are widely used all over the country. Fermented plant beverages (FPB) are prevalent in Thailand and FPBs are believed to cure and prevent many health oriented problems. The people of Thailand produce many varieties of FPBs in small scale or large scale and consume them in their daily lives. This study is a survey conducted among the representative consumers of FPBs in Thailand to know the consumer’s opinion on FPBs, effects and benefits of FPBs, and real status of consumer satisfaction in Thailand. This study revealed that the rationale for the consumption of respective FPBs was to treat their health issues and for the betterment of their health. Most of the consumers of FPBs benefited in case of improving their physical and mental health. The current survey revealed the opinion of the FPBs consumers in Thailand. This study concluded that FPBs are health promoting drink that is affordable in the daily life of Thai people. The FPBs prepared in Thailand did not report any massive adverse effects in Thailand. Till now the preparation and consumption of FPBs are followed in Thailand and not influenced by adverse effects; FPBs are considered safe for human consumption.